A systematic review of the outcomes of sustained environmental collective action - Gulliver, Robyn E.; Star, Cassandra; Fielding, Kelly S.; Louis, Winnifred R. (Environmental science & policy, 2022)
Collective action plays a critical role in progressing efforts to protect the global environment. In this study we examined existing research that specified causal claims about the outcomes of sustained environmental collective action and analysed the collective action characteristics associated with the stated outcomes. Of the 640 studies identified in our literature search, 113 papers examined environmental collective action outcomes over a time period of one or more years. In total, 59 different environmental collective action outcomes were identified, including changing corporate/business practices (n = 16), achieving political outcomes (n = 12), fostering movement building (n = 8), development project-specific outcomes (n = 8), physical changes such as increased forest cover (n = 7), or changes in public opinion, values, or behaviours (n = 4). In terms of general outcomes (i.e., success of failure of environmental collective action) the most common outcome claimed was both success and failure (n = 44), followed by complete success (n = 37) and mostly failure (n = 18). All papers identified the use of normative collective action, while 36 papers mentioned non-violent non-normative action such as blockades and sit-ins. Across the dataset there was a lack of consistency in descriptive terminology, methodological approach and inclusion of empirical evidence in justifying causal claims. We close with recommendations for scholars’ best practices for advancing research into environmental collective action outcomes, namely: consistent terminology, mapping outcomes against goals, increased studies of failure, and diversifying studies in non-WEIRD contexts. •A systematic review of 113 studies on environmental collective action outcomes.•59 distinct outcomes are identified, including 16 corporate & 12 political.•Most studies claimed outcomes of both success & failure (n = 44) or success (n = 37).•Only 3 studies examined failed collective action & 76 focused on WEIRD contexts.•Four recommendations to guide collective action outcomes research are presented.